2020
DOI: 10.1186/s12913-020-05220-7
|View full text |Cite
|
Sign up to set email alerts
|

Resource implications of the latent tuberculosis cascade of care: a time and motion study in five countries

Abstract: Background: The End TB Strategy calls for global scale-up of preventive treatment for latent tuberculosis infection (LTBI), but little information is available about the associated human resource requirements. Our study aimed to quantify the healthcare worker (HCW) time needed to perform the tasks associated with each step along the LTBI cascade of care for household contacts of TB patients. Methods: We conducted a time and motion (TAM) study between January 2018 and March 2019, in which consenting HCWs were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Cost of medication for active TB 674 RAMQ 28 Cost of medication for latent TB 114 RAMQ 28 Cost of visits to manage active TB treatment 436 FIQ, 29 Alsdurf et al 30 Cost of visits to manage LTBI treatment 42 FIQ, 29 Alsdurf et al, 30 Campbell et al 31 Cost of severe adverse event caused by active TB treatment 16 364 Tan et al 20 Cost of adverse event during LTBI treatment 782 Campbell et al 31 Cost of medical evacuation 6713 Banerji et al 32 Cost of hospital stay per day 2050 NRBHSS 33 Note: FIQ = Fédération Interprofessionelle de la santé du Québec, LTBI = latent tuberculosis infection, NRBHSS = Nunavik Regional Board of Health and Social Services, RAMQ = Régie de l'assurance maladie du Québec, TB = tuberculosis. *These costs are specific to Village 1 (there were 604 people screened in Village 1).…”
Section: Cost Related To Management Of Active Tb and Ltbimentioning
confidence: 99%
“…Cost of medication for active TB 674 RAMQ 28 Cost of medication for latent TB 114 RAMQ 28 Cost of visits to manage active TB treatment 436 FIQ, 29 Alsdurf et al 30 Cost of visits to manage LTBI treatment 42 FIQ, 29 Alsdurf et al, 30 Campbell et al 31 Cost of severe adverse event caused by active TB treatment 16 364 Tan et al 20 Cost of adverse event during LTBI treatment 782 Campbell et al 31 Cost of medical evacuation 6713 Banerji et al 32 Cost of hospital stay per day 2050 NRBHSS 33 Note: FIQ = Fédération Interprofessionelle de la santé du Québec, LTBI = latent tuberculosis infection, NRBHSS = Nunavik Regional Board of Health and Social Services, RAMQ = Régie de l'assurance maladie du Québec, TB = tuberculosis. *These costs are specific to Village 1 (there were 604 people screened in Village 1).…”
Section: Cost Related To Management Of Active Tb and Ltbimentioning
confidence: 99%
“…Swindells et al reported 512 attempts to reach 308 households for contact investigation, requiring a median time of four hours of staff person-time per attempt across sites in eight countries [23] . Alsdurf and colleagues estimated the time required for health care workers to complete all steps of evaluation of household contacts to be 1·8 hours to 5·2 hours per TB positive patient, though this estimate included steps for tuberculin skin test placement and reading, which may not be conducted in all settings [24] . Engaging community health workers may support this effort; Zawedde-Muyanja et al found improvements in screening of household contacts and initiation and completion of TPT among children in Uganda following training of community health workers [25] .…”
Section: Discussionmentioning
confidence: 99%
“…All healthcare activities associated with diagnosis of TBI and exclusion of TBD is recorded for each of the three strategies. The healthcare personnel time spent for each of these activities will be estimated from a published time and motion study [ 24 ]. Local unit costs will be used to valuate blood tests, images test (such as CXR), and microbiological tests (smear, culture or GX).…”
Section: Methods and Analysismentioning
confidence: 99%
“…We have adapted a standardized interviewer-administered questionnaire that we used previously to measure patient and family costs associated with TBD [ 24 ]. We have included a small number of items on this questionnaire regarding patient experience and acceptability of study procedures.…”
Section: Methods and Analysismentioning
confidence: 99%